Implementasi Permendikbud Nomor 87 Tahun 2013 Tentang Program Pendidikan Profesi Guru (PPG) Di Universitas Muhammadiyah Malang - Nurinayah Nurinayah; Lud Waluyo (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to describe (1) Implementation of Permendikbud Number 87 of 2013 concerning Pre-service Teacher Professional Education (PPG); (2) Inhibiting factors in the implementation of Permendikbud Number 87 of 2013. This study uses descriptive qualitative methods. This research was conducted at the PGSD Study Program at the University of Muhammadiyah Malang. The subjects of this study were the chairperson of PPG, the chairperson of the PGSD study program, and the PPG student of the study program PGSD. The data collection techniques used were using techniques, interviews, documentation, and observation. Data analysis techniques using the Milles Huberman model, with the stages of reduction, presentation, and concluding. Test the validity of the data using source triangulation. The results showed (1) Implementation of Permendikbud Number 87 of 2013 in the implementation of PPG through learning activities in the classroom, in the dormitory, and field practice in schools. The purpose of this implementation is to produce professional teachers who master the four competencies, are skilled in preparing teaching materials, and motivate teachers to become professionals by continuing education. (2) The inhibiting factor in implementation is influenced by the lack of preparation of participants in participating in UTN, and K-13 based schools are inadequate.Keywords: Teacher, PPG, Minister of Education and Culture Regulation Number 87 the Year 2013 Abstrak: Penelitian ini bertujuan untuk mendeskripsikan (1) Implementasi Permendikbud Nomor 87 tahun 2013 tentang Pendidikan Profesi Guru (PPG) Prajabatan; (2) Faktor penghambat dalam implementasi permendikbud Nomor 87 tahun 2013. Penelitian ini menggunakan metode kualitatif deskriptif. Penelitian ini dilakukan di Program Studi PGSD Universitas Muhammadiyah Malang. Subjek penelitian ini adalah ketua PPG, ketua prodi PGSD, dan mahasiswa PPG prodi PGSD.Teknik pengumpulan data yang digunakan menggunakan teknik, wawancara, dokumentasi, dan observasi. Teknik analisis data menggunakan model Milles Huberman, dengan tahap reduksi, penyajian, dan menarik kesimpulan. Uji keabsahan data menggunakan triangulasi sumber. Hasil penelitian menunjukkan (1) Implementasi Permendikbud Nomor 87 Tahun 2013 dalam pelaksanaan PPG melalui kegiatan pembelajaran di dalam kelas, di asrama, dan praktik lapang di sekolah. Tujuan dalam implementasi ini yaitu utnuk mencetak guru profesional yang menguasai empat kompetensi, terampil menyiapkan bahan ajar, dan memotivasi guru untuk menjadi tenaga profesional dengan melakukan pendidikan berkelanjutan. (2) Faktor penghambat dalam implementasi dipengaruhi oleh persiapan yang kurang peserta dalam mengikuti UTN, dan sekolah yang berbasis K-13 belum memadai.Kata kunci: Guru, PPG, Permendikbud Nomor 87 Tahun 2013